Ocena wyników leczenia chronicznych bólów kręgosłupa w odcinku lędźwiowo-krzyżowym masażem klasycznym = Evaluation of the results of treatment of chronic back pain in the lumbosacral segment by use of the classical massage - Kałużna, Anna; Kałużny, Krystian; Kochański, Bartosz; Kluska, Kamil; Płoszaj, Ola; Zukow, Walery; Hagner, Wojciech (Journal of Education, Health and Sport, 2015)
Kałużna Anna, Kałużny Krystian, Kochański Bartosz, Kluska Kamil, Płoszaj Olga, Zukow Walery, Hagner Wojciech. Ocena wyników leczenia chronicznych bólów kręgosłupa w odcinku lędźwiowo-krzyżowym masażem klasycznym = Evaluation of the results of treatment of chronic back pain in the lumbosacral segment by use of the classical massage. Journal of Education, Health and Sport. 2015;5(9):577-586. ISSN 2391-8306. DOI10.5281/zenodo.31601 http://dx.doi.org/10.5281/zenodo.31601 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%289%29%3A577-586 https://pbn.nauka.gov.pl/works/638142 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011–2014http://journal.rsw.edu.pl/index.php/JHS/issue/archive Deklaracja. Specyfika i zawartość merytoryczna czasopisma nie ulega zmianie. Zgodnie z informacją MNiSW z dnia 2 czerwca 2014 r., że w roku 2014 nie będzie przeprowadzana ocena czasopism naukowych; czasopismo o zmienionym tytule otrzymuje tyle samo punktów co na wykazie czasopism naukowych z dnia 31 grudnia 2014 r. The journal has had 5 points in Ministry of Science and Higher Education of Poland parametric evaluation. Part B item 1089. (31.12.2014). © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 02.08.2015. Revised 05.09.2015. Accepted: 29.09.2015. Ocena wyników leczenia chronicznych bólów kręgosłupa w odcinku lędźwiowo-krzyżowym masażem klasycznym Evaluation of the results of treatment of chronic back pain in the lumbosacral segment by use of the classical massage Anna Kałużna1, Krystian Kałużny1, Bartosz Kochański1, Kamil Kluska1, Olga Płoszaj2, Walery Zukow3, Wojciech Hagner1 1) Katedra i Klinika Rehabilitacji, Wydział Nauk o Zdrowiu, Uniwersytet Mikołaja Kopernika w Toruniu; 2) Bydgoska Szkoła Wyższa, Bydgoszcz; 3) Instytut Kultury Fizycznej, Wydział Kultury Fizycznej, Zdrowia i Turystyki, Uniwersytet Kazimierza Wielkiego w Bydgoszczy Streszczenie Wstęp: Dolegliwości bólowe kręgosłupa są poważnym problemem zdrowotnym współczesnej medycyny. Ból kręgosłupa często jest przyczyną ograniczenia aktywności, utrudnia wykonywanie czynności dnia codziennego i znacząco obniża jakość życia. W leczeniu dolegliwości bólowych kręgosłupa stosuje się wiele form terapii, jedną z nich jest masaż klasyczny. Cel pracy: Celem pracy jest ocena wyników leczenia chronicznych bólów kręgosłupa w odcinku lędźwiowo-krzyżowym masażem klasycznym. Materiał i metody: Badania przeprowadzono na grupie 80 pacjentów (57 kobiet i 23 mężczyzn) w wieku 45-57 lat z przewlekłymi dolegliwościami bólowymi kręgosłupa. Przed rozpoczęciem terapii przeprowadzono szczegółowy wywiad i badanie wstępne z wykorzystaniem testu Otta, testu Schobera oraz skali oceny bólu VAS. Po zakończeniu serii 10 zabiegów masażu klasycznego przeprowadzono badanie końcowe – identyczne jak badanie wstępne. Wyniki: Wyniki przeprowadzonych badań wskazują na wysoką skuteczność leczenia chronicznych bólów kręgosłupa masażem klasycznym w aspekcie zmniejszenia poziomu bólu oraz poprawy zakresu ruchomości kręgosłupa. Wnioski: Seria 10 zabiegów masażu klasycznego istotnie statystycznie wpływa na zmniejszenie dolegliwości bólowych kręgosłupa w odcinku lędźwiowo-krzyżowym oraz na poprawę stanu funkcjonalnego pacjenta. Abstract Introduction: Back pain is a serious health problem of modern medicine. Back pain is often the cause of activity limitation, makes it difficult to perform activities of daily living and significantly reduces the quality of life. In the treatment of back pain use many forms of therapy, one of which is the classical massage. Aim: The aim of this study is to evaluate the results of treatment with classical massage in patients with chronic low back pain. Material and Methods: The study was conducted on a group of 80 patients (57 women and 23 men) aged 45-57 years with chronic spinal pain. Before starting therapy conducted a detailed medical history and an initial examination using Otto test , Schober test and VAS scale. After completing a series of 10 treatments of classical massage final survey was conducted - the same as the initial study. Results: Results of this study showed high efficacy classic massage therapy for chronic back pain. Observed a reduction in pain and improvement in range of motion of the spine. Conclusion: A series of 10 classical massage significantly reduces back pain in the lumbar-sacral segment and to improve the functional status of the patient. Słowa kluczowe: dolegliwości bólowe kręgosłupa, leczenie zachowawcze, masaż klasyczny. Keywords: spine aches and pains, conservative treatment, classical massage.